Comparison of simple versus complex stenting in patients with true distal left main bifurcation lesions. Issue 5 (8th September 2020) - Lee, Cheol Hyun; Ahn, Jung‐Min; Kang, Do‐Yoon; Han, Minkyu; Park, Hanbit; Lee, Pil Hyung; Lee, Seung‐Whan; Park, Seong‐Wook; Park, Duk‐Woo; Park, Seung‐Jung
Abstract: Introduction: Distal left main (LM) bifurcation disease is one of the most challenging lesion subsets for percutaneous coronary intervention (PCI) and optimal stenting strategy for such complex lesions is still debated. This study aimed to compare clinical outcomes following single versus dual stenting for true distal LM bifurcation lesions. Methods: Patients with true distal LM bifurcation lesions (type 1, 1, 1 or 0, 1, 1: both left anterior descending and circumflex artery >2.5 mm diameter) receiving PCI with drug‐eluting stents (DES) from two large clinical registries were evaluated. The primary outcome was target‐lesion failure (TLF), defined as a composite of cardiac death, target‐vessel myocardial infarction (MI), or target‐lesion revascularization (TLR). Outcomes were compared with the use of propensity scores and inverse probability‐weighting adjustment to reduce treatment selection bias. Results: Among 1, 002 patients undergoing true distal LM PCI, 440 (43.9%) and 562 (56.1%) were treated with single and dual stents, respectively. The TLF rates at 3 year was 20.3% in the single‐stent group and 24.1% in the dual‐stenting group (log‐rank p = 0.18). The adjusted risk for TLF did not differ significantly between two groups (hazard ratio [HR] with dual‐stent vs. single‐stent: 1.27, 95% confidence interval [CI]: 0.95–1.71). The adjusted risks for death, MI, repeat revascularization, or stent thrombosis were also similar between the single‐ and dual‐stenting groups. Conclusions: In patients undergoing PCI for true distal LM disease, single‐ and dual‐stent strategies showed a similar adjusted risk of TLF at 3 years. Our findings should be confirmed or refuted through large, randomized clinical trials.